2022
DOI: 10.1136/jitc-2021-003731
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CCR4 treatment depletes regulatory T cells and leads to clinical activity in a canine model of advanced prostate cancer

Abstract: BackgroundTargeting regulatory T cell (Treg) infiltration is an emerging strategy for cancer immunotherapy. However, its efficacy in advanced prostate cancer remains unclear. Here, we showed the therapeutic efficacy of anti-Treg treatment in a canine model of advanced prostate cancer.MethodsWe used dogs with naturally occurring prostate cancer to study the molecular mechanism underlying Treg infiltration and the effect of anti-Treg treatment. Tumor-infiltrating Tregs was evaluated by immunohistochemistry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…For canine prostate cancer, recent evidence shows that T and B lymphocytes are increased in the tissue and that intra-tumor CD3+ TILs and granzyme B+ cell estimation are correlated with survival [ 127 , 129 ]. Also, it has been shown that increased Tregs are associated with poor prognosis showing parallels with what is observed in human tumors [ 128 , 170 ].…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 69%
“…For canine prostate cancer, recent evidence shows that T and B lymphocytes are increased in the tissue and that intra-tumor CD3+ TILs and granzyme B+ cell estimation are correlated with survival [ 127 , 129 ]. Also, it has been shown that increased Tregs are associated with poor prognosis showing parallels with what is observed in human tumors [ 128 , 170 ].…”
Section: Tumor-infiltrating Lymphocytesmentioning
confidence: 69%
“…It would also be interesting to study the effects of the timing and duration of such a Treg-targeting antibody treatment, to determine whether it is critical for the differential control of Treg and effector T cells, in other words, whether the longer the treatment, the more likely effector T cells are to be depleted, thereby hindering the generation of effective tumor immunity [ 18 , 35 ]. The anti-CCR4 antibody, mogamulizumab, has demonstrated an effective reduction in the frequency of effector Tregs that selectively augment the induction of tumor antigen-specific CD4 + and CD8 + T cells in vivo [ 36 , 37 ].…”
Section: Tregsmentioning
confidence: 99%
“…Increased CCR4 expression is observed in activated Treg cells. Inhibition of CCR4 has been shown to reduce Treg cells accumulation, potentiate anti-tumour immune activity, sensitize tumours to PD-1 blockade and improve survival (53)(54)(55)(56). CCL5, activated by cancer FOXP3, is responsible for FOXP3 + Treg cells infiltration in pancreatic ductal adenocarcinoma (57).…”
Section: Foxp3+ Treg Cells and The Immune Escape Of Cancermentioning
confidence: 99%